Back Cover: Biomass‐assisted Zeolite Syntheses as a Tool for Designing New Acid Catalysts (ChemCatChem 12/2017). Issue 12 (22nd June 2017) - Louis, Benoît; Gomes, Elisa S.; Losch, Pit; Lutzweiler, Gaëtan; Coelho, Tiago; Faro, Arnaldo; Pinto, Joana F.; Cardoso, Cristiane S.; Silva, Alessandra V.; Pereira, Marcelo M.
Abstract : The Cover shows an alternative route involving sugar cane‐derived biomass to produce zeolites with tailored properties.In their Concept, B. Louis et al. highlight the impact of the presence of sugars, lignin, biomass hydrolysates and biomass residues on the crystallization of various zeolite structures. The presence of those biosourced secondary templates (BSST) induces morphological/textural changes and, sometimes, modifications of the chemical composition and acidic properties. The BSST strategy may serve as a basis for the rational synthesis of heterogeneous catalysts. More information can be found in the Concept by B. Louis et al. onpage 2065 in Issue 12, 2017 (DOI:10.1002/cctc.201700062 ).